2017
DOI: 10.1007/s00018-017-2540-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of G3BP1 in glucocorticoid receptor-mediated microRNA-15b and microRNA-23a biogenesis in endothelial cells

Abstract: MicroRNAs (miRNAs) are a family of non-coding RNAs that play crucial roles in regulating various normal cellular responses. Recent studies revealed that the canonical miRNA biogenesis pathway is subject to sophisticated regulation. Hormonal control of miRNA biogenesis by androgen and estrogen has been demonstrated, but the direct effects of the glucocorticoid receptor (GR) on miRNA biogenesis are unknown. This study revealed the role of GR in miRNA maturation. We showed that two GR agonists, dexamethasone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…For miRNA measurement, TaqMan MicroRNA reverse transcription stem-loop primers were used according to the manufacturer's protocol and all real-time PCR reactions were determined on a StepOnePlus PCR system. The PCR mix was denatured at 95°C for 10 min, followed by 40 cycles of melting at 95°C for 15 s and annealing at 60°C for 60 s (Kwok et al, 2017 ). The internal control U6 was determined in parallel and used to normalize the relative expression of miR-33a expression.…”
Section: Methodsmentioning
confidence: 99%
“…For miRNA measurement, TaqMan MicroRNA reverse transcription stem-loop primers were used according to the manufacturer's protocol and all real-time PCR reactions were determined on a StepOnePlus PCR system. The PCR mix was denatured at 95°C for 10 min, followed by 40 cycles of melting at 95°C for 15 s and annealing at 60°C for 60 s (Kwok et al, 2017 ). The internal control U6 was determined in parallel and used to normalize the relative expression of miR-33a expression.…”
Section: Methodsmentioning
confidence: 99%
“…G3BP1 also regulates the maturation of the glucocorticoid receptor (GR) regulated miRNAs. It binds to primary miR-15b~16-2 and miR-23a~27a~24-2 through its consensus sequence and restricts their maturation in endothelial cells [69]. G3BP1 is also involved in the regulation of neuronal genes by regulating non-coding (NC) RNAs, including intron retaining transcripts.…”
Section: G3bps and Micrornas (Mirnas)mentioning
confidence: 99%
“…Further, the study in EC GR-deficient mice (GR EC KO ) revealed that the expression of eNOS and inducible nitric oxide synthase was increased, leading to NO release in sepsis (Goodwin et al 2013). In addition, GR agonists dexamethasone and ginsenoside-Rg1 rapidly suppressed the expression of mature miRNA-15b, miRNA-23a and miRNA-214 in human endothelial cells, which may mediate acute cardiovascular protective effects (Kwok et al 2017). The data form adult endothelial cells could give us some clues for the regulation of glucocorticoids on developing endothelial cells, especially under maternal stress.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Several miRNAs have been implicated in positive or negative regulation of inflammatory responses in immune cells (Sheedy et al 2008, O'Connell et al 2010, which may be subject to modulation by glucocorticoids. Recently, RNA pulldown coupled with proteomic analysis recognized that GTPase-activating protein (SH3 domain)-binding protein 1 (G3BP1) mediates GR-regulated miRNA maturation (Kwok et al 2017). Activated GR-induced phosphorylation of v-AKT murine thymoma viral oncogene homologue kinase, which in turn phosphorylated and promoted nuclear translocation of G3BP1.…”
Section: Mirnasmentioning
confidence: 99%
See 1 more Smart Citation